The Efficiency of Internet Base Healthcare System in Gastroenterological diseases: An Updated Systematic Review - Amin Elzaki, Hanan Elnour, Mona Elhaj, Samih Kajoak, Amel F H Alzain, (Pakistan Journal of Medical & Health Sciences, 2022)
Digital health systems such as tablet devices, smartphones, and online websites, are swiftly transforming the practice of medical science and reshaping health care approaches. A PRISMA guidelines-based systematic review was conducted using research databases (PubMed, Google Scholar, and Web of Science) to identify the applications and fill the literature gap in Gastroenterological disorders. A total of 212 articles were searched, excluding duplicate records, sixty nine articles were founded out of which only fifteen were selected using specific inclusion and exclusion criteria. Risk of a bias assessment tool called ROBVIS 2 is used to examine the risk of predisposition and precision of all the fifteen studies included. Most of the patients in these trials were females, educated, and have inflammatory bowel diseases. These clinical studies concentrated on Ulcerative colitis (n=5), Crohn's disease (n=4), and inflammatory bowel disease (n=6) with feedback of mostly 3 months (n=5) and 6 months (n=5). The internet-based intervention varied from study to study but the outcomes in each study were clear that either this system was efficient or not. Based on the searched literature and selected studies it was concluded that online health technologies can effectively cope with Gastroenterological disorders and patients with digestive disorders have shown good acceptability and pleasure in all the selected studies.